2003
DOI: 10.1109/tec.2003.815851
|View full text |Cite
|
Sign up to set email alerts
|

A novel detection method of motor broken rotor bars based on wavelet ridge

Abstract: Detection of cage motor broken rotor bars has long been an important but difficult job in the detection area of motor faults. The characteristic frequency component of faulted rotor (CFCFR) is very close to the power frequency component but by far less in amplitude, which brings about great difficulty for accurate detection. A new detection method based on wavelet ridge is presented in this paper. Aiming at the motor's starting period during which the motor accelerates progressively and CFCFR approaches the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…However, these extra components fade away or coincide with other components, like saturationinduced components that do not contain information related to the fault, when the motor reaches steady state [39]. One of the challenges of using the current during startup, and one of the main reasons why it has not been commonly used for fault detection, is the complexity of extracting fault characteristics as the startup current is extremely unsteady and its period is quite short [40]. Recent analysis of transient current signature in induction motors [28,29] has shown that transient stator current is independent of load conditions that make it suitable for fault detection.…”
Section: Line Start Permanent Magnet Synchronousmentioning
confidence: 99%
“…However, these extra components fade away or coincide with other components, like saturationinduced components that do not contain information related to the fault, when the motor reaches steady state [39]. One of the challenges of using the current during startup, and one of the main reasons why it has not been commonly used for fault detection, is the complexity of extracting fault characteristics as the startup current is extremely unsteady and its period is quite short [40]. Recent analysis of transient current signature in induction motors [28,29] has shown that transient stator current is independent of load conditions that make it suitable for fault detection.…”
Section: Line Start Permanent Magnet Synchronousmentioning
confidence: 99%
“…wavelet polar maps, are used for gear fault diagnostics, to display wavelet amplitude and phase. The detection of broken rotor bars in induction machines by using CWT analysis of current waveforms was presented in Zhang et al (2003) …”
Section: Waveletsmentioning
confidence: 99%
“…Several MCSA-based techniques have been proposed in literature for BRB fault detection, based on spectral analysis of sidebands of the power frequency or its harmonics using methods such as multiresolution Taylor-Kalman approach [5], low-frequency load torque oscillations [6], auto-regression analysis [7], autoregressive-spectrum analysis [8] and high-resolution parameter estimation [9]. However, similar sidebands can also occur in spectral maps of healthy motors due to rotor asymmetries caused by manufacturing/assembly tolerances and connection coupling.…”
Section: Introductionmentioning
confidence: 99%